Cytotoxic activity of marine algae against cancerous cells - Guedes,Élica A. C. (2013)
This paper presents an investigation on the cytotoxic activity in human tumor cell from dichloromethane, chloroform, methanol, ethanol, water extracts, and hexane and chloroform fractions from green, brown and red algae collected at Riacho Doce Beach, north coast of Alagoas, Brazil, against the cancer cells K562 (chronic myelocytic leukemia), HEp-2 (laryngeal epidermoid carcinoma) and NCI-H292 (human lung mucoepidermoid carcinoma) through the MTT colorimetric method. The dichloromethane extract and chloroform fraction of Hypnea musciformis showed the best cytotoxic activity against K562 (3.8±0.2 µg.mL-1 and 6.4±0.4 µg.mL-1, respectively). Dichloromethane extracts of Dictyota dichotoma (16.3±0.3 µg.mL-1) and the chloroform fraction of H. musciformis (6.0±0.03 µg.mL-1) and chloroform fraction of P. gymnospora (8.2±0.4) were more active against HEp-2 as well as ethanol extracts of P. gymnospora (15.9±2.8 µg.mL-1) and chloroform fraction of H. musciformis (15.0±1.3 µg.mL-1) against the cell NCI-H292. The constituents with higher anticancer action are present in the extracts of dichloromethane and chloroform and in the chloroform fraction of H. musciformis, Digenea simplex, P. gymnospora, and D.dichotoma. In the case of the seaweed S. vulgare, the anticancer constituents are present in the aqueous extract.